Educação estética com educadoras : proposta de intervenção a partir de vivências corporais - Madalóz, Rodrigo José (2011)
The research developed in the line of Educational and Languages Processes characterized by a qualitative study of comprehensive-interpretive nature, using the paradigm symbiosinergetic and inventive (BERTRAND; VALOIS; 1994). Investigate the meanings which body experiences had in the educated aesthetic process of teachers from early childhood education and early years, aiming to know and understand the trajectory of these teachers training body; body experiences create opportunities through practical experiences and individual and group; facilitate the externalization of gestures and body language free,creating different situations and proposing improvisation situations in front of daily challenges. The research involved eight teachers, one from early childhood education, two from the 1st year, two from the 2ndyear, two from the 3rd-year and one from the 4th-year, that work in a public elementary school in the city of Palmeira das Missões, RS. The educators participated in eight meetings with two yours duration each, from March to May 2011, structures in three stages. 1st awareness, 2nd body activity and 3rd relaxation. To the data collection and information s were used participant observation, field diary, data-sheet (MOLINA NETO; TRIVIÑOS, 1999) and iconographic text. For registration and further understanding based on reading transtextual unique images (LTSI), developed by Ormezzano (2009). The body experiences meant to them the possibility of establishing harmony between body and environment; changes in concepts, attitudes, transformations and practice renewal; sharing; perceive the necessity and importance of play in children s lives; feelings and sensations renewed about you and the other; movement; sparked the creativity, self-knowledge, knowledge and appreciation of the body; the essence of each one; the peace of mind; the return to childhood; meant delivery, sensitivity to life